Quantificação de bactérias entéricas em sítios anatômicos e líquido intervalvar de ostras (Crassostrea rhizophorae) e caracterização de isolados de Escherichia coli - Araújo, Rayza Lima (2013)
Fecal coliforms have been described as one of the best indicators of pollution in the aquatic environments by human wastes, and it is widely used as a parameter for classifying areas where oysters are farmed or extracted. Among Enterobacteriaceae members, E. coli stands out as potential pathogenic specie, representing risk for public healthy when associated with consumption of raw or undercooked bivalves. However, little is known about this colonization in the bivalve tissues and/or distribution of these enteric bacteria. The objective of the present study was to: (i) quantify fecal coliforms from body fluid and anatomical sites, separately; (ii) isolate and identify E. coli in oysters commercialized in natura in Praia do Futuro beach, Fortaleza-Ceará; (iii) evaluate the virulence profile and resistance to antimicrobial agents of E. coli isolates. The study covered ten samples, from February to April 2012, by analyzing twelve oysters for sample, divided into a body fluid (intervalvar liquor) and two anatomical sites (mantle and gastrointestinal tract). Fecal coliforms concentration was higher than allowed by legislation nº 12/2001 of ANVISA in three samples, and intervalvar liquor presented higher MPN in six samples. Out of 137 E. coli strains isolated, 19% was resistant to both tetracycline and oxytetracycline, and MAR ranged from 0,250 to 0,625. It is further noted producing expended spectrum beta lactamases strains, however none showed biofilm production. The major frequency resistance to oxytetracycline suggests a selective pressure to mangrove ecosystem microbiota that could be directly affected by farming shrimp activity, practiced in a region next to Parnaíba city, located in Piauí state, where oysters are extracted. In addition, the presence of multiple resistance can be a risk for in natura oyster consumers.